Ballets for the Bourgeois - McGowan, Margaret M. 1931- (Edinburgh: Edinburgh University Press, 2001)
RESUMEN: The ballet de cour, as its name implies, was essentially an aristocratic genre danced by kings, queens and courtiers for their own entertainment. It flourished as long as princes continued to rank dancing as the highest accomplishment, then it was transformed. Such a view, though generally accurate, does not give a complete account. Danced entertainments in early modern Europe extended beyond the confines of courts; they invaded the public theatres, and they involved interchange between city councils and the king (or his representative). There were frequent performances in private town and country house, not all of them belonging to noblemen. Attemtps to give a fuller picture have been frustrated by lack of evidence, contemporary sources offering only tantalizing glimpses and brief insights; there is however, a resources which has not been fully exploited - the Registres et deliberations de la ville de Paris where one finds accounts of royal performances for the burghers of Paris and their wives. These reports amplify the evidence found in writers of memoirs who conscientiously noted their own participation in ballets de cour, but rarely gave precise indications of performances other than at court.